Heat treatment effect on the phase and morphology of NiO-BCZY prepared by an evaporation and decomposition of solution and suspension method - Abdullah Abdul Samat,; Shazana Mohd Senari,; Mahendra Rao Somalu,; Andanastuti Muchtar,; Oskar Hasdinor Hassan,; Nafisah Osman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A nitrate-based nickel salt was used to prepare NiO-BaCe0.54Zr0.36Y0.1O2.95 (NiO-BCZY) composite powders by an evaporation and decomposition of solution and suspension (EDSS) method. The prepared powders with different weight ratios of NiO to BCZY (NiO:BCZY) were denoted as S1 (50:50) and S2 (60:40). The powders were characterized using Thermogravimertic analyzer (TGA), X-ray diffractometer (XRD) and scanning electron microscope (SEM) equipped with energy dispersive X-ray (EDX) spectrometer. TGA results showed that the thermal decomposition of intermediate compounds in the dried powder (T = 150°C) completed at ~700°C. XRD analysis confirmed that the calcined powder (T = 1100°C) of S1 and S2 did not show any crystalline peaks related to BCZY compound as the peaks associated to impurity phases of BaCeO3 and BaZrO3 were appeared in their XRD patterns. The impurity phases along with NiO still remained in the S1 sample after it was calcined at 1400°C. As the calcination temperature increased, the particles size of S1 also increased and Zr elemental composition deviates from the nominal stoichiometric of the NiO-BCZY as proven by SEM/EDX analysis. The results indicate that the formation of homogenize NiO-BCZY composite prepared using EDSS method was not favored even after calcined at high temperature (T = 1400°C).